2009
DOI: 10.1093/ntr/ntp067
|View full text |Cite
|
Sign up to set email alerts
|

Attentional bias modification in tobacco smokers

Abstract: These results add to a growing body of literature that suggests that a single session of ABM does not produce generalizable effects, and effects on craving and drug seeking are inconsistent across studies. Theoretical implications and directions for future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
114
3
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(131 citation statements)
references
References 39 publications
13
114
3
1
Order By: Relevance
“…This suggests that participants need not be consciously aware of the re-training to show its intended effects, consistent with findings from previous attentional bias modification studies on alcohol (Field & Eastwood, 2005;Field, Duka, Tyler & Schoenmakers, 2009). …”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This suggests that participants need not be consciously aware of the re-training to show its intended effects, consistent with findings from previous attentional bias modification studies on alcohol (Field & Eastwood, 2005;Field, Duka, Tyler & Schoenmakers, 2009). …”
Section: Discussionsupporting
confidence: 86%
“…While some have found that training effects were restricted to participants who were aware of the experimental contingencies (Attwood, O'Sullivan, Leonards, Mackinstosh & Munafo, 2008;Field et al, 2007), others found that contingency awareness did not influence training effects (Field & Eastwood, 2005;Field, Duka, Tyler & Schoenmakers, 2009). Training.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…55 Finally, of the two studies that compared attend (to drug), avoid (to drug) and control groups, the study with tobacco smokers found post-test differences between groups only for old stimuli, with a higher AB in the attend than in the other groups, but no differences between the avoid and control groups. However, this difference did not remain on the following day, 12 and ABM had no effects on subjective craving or behavioral measures of tobacco seeking. The study about alcohol users 9 found differences, as AB increased in the attend group (alcohol) from pre-to post-test, and this effect was clear for both old and new stimuli.…”
Section: Anxietymentioning
confidence: 79%
“…11,12 Of the techniques to achieve ABM included in studies, the most commonly used is a modified version of a visual probe task developed in 2002. 7 In the standard visual probe task to assess attentional bias, 13 a pair of images, one related to the pathology (target) and one control, originally from the same context of the target but which does not offer any clues to the pathology, are displayed side by side simultaneously on the screen of a computer.…”
Section: Introductionmentioning
confidence: 99%